ANALISA DISTRIBUSI TEKANAN UDARA YANG MELEWATI ELBOW 900 - Gunawan, Yuspian; Hasbi, Muhammad; Sakti Jaya, Muh (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The rapid development of a variety of disciplines to encourage the advance of civilization of human life. Use elbow in the system design perpipan causing a loss of pressure in the flow. It because by a change in direction of fluid flow through the channel. The pressure drop (pressure drop) to flow past the elbow is greater compared with a straight pipe of the same length. The size of the drop in pressure (pressure drop) to flow through the elbow is affected by the magnitude of the radius of curvature and angle of the bend of the elbow itself that caused the separation (separation loss) and secondary school (secondary flow) on the elbow 900. From the results of this study concluded that the pressure distribution at Re 8.1737 x104 is smaller than Re 10, 1467 x104, while pressure on Losses Re 8.1737 x104 is smaller than Re 10.1467 x104. Keywords: Distribution analysis, air pressure, and elbow 900.